Building measurement : new rules of measurement / Andrew Packer - Packer, Andrew
In this much-needed new measurement textbook, the measurement of the most common building elements is described using NRM2. Extensive worked examples including fully up to date hand-drawn diagrams and supporting take-off lists ensure that the reader develops a confidence in their ability to measure using NRM2 in practice.